Mosquito and sand fly gregarines of the genus Ascogregarina and Psychodiella (Apicomplexa: Eugregarinorida, Aseptatorina)--overview of their taxonomy, life cycle, host specificity and pathogenicity - Lantova, Lucie; Volf, Petr (Infection, genetics and evolution, 2014)
Mosquitoes and sand flies are important blood-sucking vectors of human diseases such as malaria or leishmaniasis. Nevertheless, these insects also carry their own parasites, such as gregarines; these monoxenous pathogens are found exclusively in invertebrates, and some of them have been considered useful in biological control. Mosquito and sand fly gregarines originally belonging to a single genus Ascogregarina were recently divided into two genera, Ascogregarina comprising parasites of mosquitoes, bat flies, hump-backed flies and fleas and Psychodiella parasitizing sand flies. Currently, nine mosquito Ascogregarina and five Psychodiella species are described. These gregarines go through an extraordinarily interesting life cycle; the mosquito and sand fly larvae become infected by oocysts, the development continues transtadially through the larval and pupal stages to adults and is followed by transmission to the offspring by genus specific mechanisms. In adult mosquitoes, ascogregarines develop in the Malpighian tubules, and oocysts are defecated, while in the sand flies, the gregarines are located in the body cavity, their oocysts are injected into the accessory glands of females and released during oviposition. These life history differences are strongly supported by phylogenetical study of SSU rDNA proving disparate position of Ascogregarina and Psychodiella gregarines. This work reviews the current knowledge about Ascogregarina and Psychodiella gregarines parasitizing mosquitoes and sand flies, respectively. It gives a comprehensive insight into their taxonomy, life cycle, host specificity and pathogenicity, showing a very close relationship of gregarines with their hosts, which suggests a long and strong parasite-host coevolution.
Keywords: Psychodidae; Culicidae; mužské pohlaví; Life Cycle Stages; ženské pohlaví; Host Specificity; Host-Parasite Interactions; Animals; zvířata; Male; Female; stadia vývoje; Host-Pathogen Interactions; interakce hostitele a parazita; hostitelská specificita; interakce hostitele a patogenu